Pengaruh Struktur Modal, Ukuran Perusahaan, Kebijakan Dividen dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Sektor Properties dan Real Estate yang Terdaftar di BEI Periode 2019-2023 - Manalu, Cindi Elisabeth; Gultom, Robinhot; Purba, Jon Henri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to test and analyze how the influence of Capital Structure, Company Size, Dividend Policy and Profitability on the Value of Properties and Real Estate Companies listed on the Indonesia Stock Exchange in 2019-2023. The variables used in this study, the independent variable (X) consists of Capital Structure proxied by Debt to Equity ratio (DER), Company Size proxied by (Ln Total Asset), Dividend Policy proxied by Dividend Payout Ratio (DPR), and Profitability proxied by Return On Assets (ROA). The sample in this study was obtained by the purposive method. Based on the criteria and data processing process that have been set, 55 companies were determined as research samples. The data analysis technique used is multiple linear regression. The results of this study state that partially Capital Structure (DER) does not have a significant effect on Company Value, Company Size (Ln Total Asset) has a significant negative effect on Company Value, Dividend Policy (DPR) does not have a significant effect on Company Value and Profitability (ROA) has a positive and significant effect on Company Value. Simultaneously Capital Structure, Company Size, Dividend Policy, and Profitability have a significant effect on Company Value.